Adult Hippocampal Neurogenesis and Plasticity in the Infrapyramidal Bundle of the Mossy Fiber Projection: I. Co-Regulation by Activity - Römer, Benedikt; Krebs, Julia; Overall, Rupert W.; Fabel, Klaus; Babu, Harish; Overstreet-Wadiche, Linda; Brandt, Moritz; Williams, Robert W.; Jessberger, Sebastian; Kempermann, Gerd (Frontiers in Neuroscience, 2011)
Besides the massive plasticity at the level of synapses, we find in the hippocampus of adult mice and rats two systems with very strong macroscopic structural plasticity: adult neurogenesis, that is the lifelong generation of new granule cells, and dynamic changes in the mossy fibers linking the dentate gyrus to area CA3. In particular the anatomy of the infrapyramidal mossy fiber tract (IMF) changes in response to a variety of extrinsic and intrinsic stimuli. Because mossy fibers are the axons of granule cells, the question arises whether these two types of plasticity are linked. Using immunohistochemistry for markers associated with axonal growth and pro-opiomelanocortin (POMC)–GFP mice to visualize the post-mitotic maturation phase of adult hippocampal neurogenesis, we found that newly generated mossy fibers preferentially but not exclusively contribute to the IMF. The neurogenic stimulus of an enriched environment increased the volume of the IMF. In addition, the IMF grew with a time course consistent with axonal outgrowth from the newborn neurons after the induction of neurogenic seizures using kainate. These results indicate that two aspects of plasticity in the adult hippocampus, mossy fiber size and neurogenesis, are related and may share underlying mechanisms. In a second part of this study, published separately (Krebs et al., 2011) we have addressed the question of whether there is a shared genetics underlying both traits.